Genetic identification of the sharks Rhizoprionodon porosus and R. lalandii by PCR-RFLP and nucleotide sequence analyses of 5S rDNA - Pinhal, Danillo [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Martins, Cesar [UNESP] (Springer, 2009)
A molecular approach based on nuclear 5S rDNA sequence variability was applied successfully to correctly identify samples from the two Rhizoprionodon species collected in the wild or sold in markets. The sequence of the non-transcribed spacer (NTS) of the 5S rDNA showed high interspecific variability and no intra-specific polymorphism, making it a useful marker for sharpnose shark identification. Polymorphisms in the NTS sequences of Rhizoprionodon sharks also created unique restriction patterns for each species after PCR-RFLP analysis. The 5S rDNA polymorphism represents a fast and non expensive tool to access species identification when rapid and unequivocal identification of shark products is needed, particularly for future management and other investigations.
Keywords: Genetic markers; Non-transcribed spacer; Trade monitoring; Sharks; Species identification